Dynamics of nitrogenase cofactor elements and resource limitation of asymbiotic biological nitrogen-fixation during long-term pedogenesis - O. M. Butler; G. Liang; S. Matsumura; C. R. Chen; B. Kaiser; C. R. Warren (Plant and Soil, 2026)
Background and aims Biological nitrogen fixation (BNF) is central to long-term pedogenesis and overall terrestrial ecosystem development. Rates of asymbiotic BNF are potentially constrained by carbon (C), phosphorus (P), and/or nitrogenase cofactor elements (e.g., iron [Fe], vanadium [V], and molybdenum [Mo]), but our understanding of the biogeochemical trajectories of cofactor elements throughout pedogenesis is limited. Methods Using a ~ 700 ka pedogenic chronosequence at Cooloola in eastern Australia, we quantified P, Fe, V, and Mo in soil and litter and tested for C (i.e., energy), P, and/or Mo limitation of asymbiotic BNF using acetylene reduction assays. Results Cofactor elements in soil declined faster than P during pedogenesis, and their relative extractability with chelating agents increased across the chronosequence. Addition of C, P, and/or Mo did not affect asymbiotic BNF in any dune system tested. Conclusion Declines of soil P and cofactor elements during pedogenesis support an underlying influence of weathering on the biogeochemical cycling of these elements. However, dynamics of Fe, V, and Mo diverge from those of P due to increasing chelation by SOM as podzolization advances, whereas P is increasingly present in organic forms. Asymbiotic BNF is seemingly not limited by C, P, or Mo during pedogenesis at Cooloola.

A pragmatic framework for local operationalisation of national-level biodiversity impact mitigation commitments - Thomas B. Atkins; Natalie E. Duffus; Amber J. Butler; Hannah C. Nicholas; Sophus O.S.E. zu Ermgassen; Prue Addison; E.J. Milner-Gulland (Environmental Science & Policy, 2025)

Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Thermal exposure risk in different life stages of Chinook salmon in the Nechako River system, British Columbia - Muhammed A. Oyinlola; Mostafa Khorsandi; Noa B. Mayer; Natalie Butler; Jacey C. Van Wert; Erika J. Eliason; Richard Arsenault; Colin J. Brauner; Scott G. Hinch; Andre St-Hilaire (Climatic Change, 2024)

Refining spiny lobster (Panulirus argus) escape and mortality estimates in Florida’s lobster trap fishery using long-term video - Casey B. Butler; Jack Butler; William C. Sharp; Thomas R. Matthews (Fisheries Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Accumulation and transport of nutrient and pollutant elements in riparian soils, sediments, and river waters across the Thames River Watershed, Connecticut, USA - Mark J. Butler; Brian C. Yellen; Oluyinka Oyewumi; William Ouimet; Justin B. Richardson (Science of The Total Environment, 2023)

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Trace metals and metalloids in peri-urban soil and foliage across geologic materials, ecosystems, and development intensities in Southern California - Trevor J. Mackowiak; Ivan C. Mischenko; Mark J. Butler; Justin B. Richardson (Journal of Soils and Sediments, 2021)

Seasonal, lunar, and diel patterns in spawning by the giant barrel sponge, Xestospongia muta - K. L. Neely; C. B. Butler (Coral Reefs, 2020)

Chromium, manganese, nickel, and cobalt mobility and bioavailability from mafic-to-ultramafic mine spoil weathering in western Massachusetts, USA - Justin A. Mistikawy; Trevor J. Mackowiak; Mark J. Butler; Ivan C. Mischenko; Richard S. Cernak; Justin B. Richardson (Environmental Geochemistry and Health, 2020)

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Biophysical connectivity explains population genetic structure in a highly dispersive marine species - Nathan K. Truelove; Andrew S. Kough; Donald C. Behringer; Claire B. Paris; Stephen J. Box; Richard F. Preziosi; Mark J. Butler (Coral Reefs, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Wheat cultivar susceptibility to Gaeumannomyces graminis var. tritici and influence on Pseudomonas fluorescence numbers in the rhizosphere - R. F. van Toor; S. Chng; R. M. Warren; R. C. Butler; M. G. Cromey; R. A. Craigie; B. L. McCloy (Australasian Plant Pathology, 2016)

Molecular and morphological insights into the origin of the invasive greater white-toothed shrew (Crocidura russula) in Ireland - Laura M. Gargan; Raphaël Cornette; Jon M. Yearsley; W. Ian Montgomery; Joana Paupério; Paulo C. Alves; Fidelma Butler; Michel Pascal; Anne Tresset; Anthony Herrel; John Lusby; David G. Tosh; et al. (Biological Invasions, 2016)

2nd International Conference on Progressive Multifocal Leukoencephalopathy (PML) 2015: JCV virology, progressive multifocal leukoencephalopathy pathogenesis, diagnosis and risk stratification, and new approaches to prevention and treatment - Andriani C. Patera; Scott L. Butler; Paola Cinque; David B. Clifford; Robert Elston; Robert L. Garcea; Eugene O. Major; Dejan Pavlovic; Ilse S. Peterson; Anne M. Ryan; Kenneth L. Tyler; Thomas Weber (Journal of NeuroVirology, 2015)

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Wild Turkey (Meleagris gallopavo) association to roads: implications for distance sampling - Devin R. Erxleben; Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Markus J. Peterson; Nova J. Silvy; William P. Kuvlesky; David G. Hewitt; Stephen J. DeMaso; Jason B. Hardin; Megan K. Dominguez-Brazil (European Journal of Wildlife Research, 2011)

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Wild turkey (Meleagris gallopavo) detectability from helicopters and ramifications for estimating abundance - Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Stephen J. DeMaso (European Journal of Wildlife Research, 2008)

Finite-Element Stress Analysis of a Multicomponent Model of Sheared and Focally-Adhered Endothelial Cells - Michael C. Ferko; Amit Bhatnagar; Mariana B. Garcia; Peter J. Butler (Annals of Biomedical Engineering, 2007)

Finite-Element Stress Analysis of a Multicomponent Model of Sheared and Focally-Adhered Endothelial Cells - Michael C. Ferko; Amit Bhatnagar; Mariana B. Garcia; Peter J. Butler (Annals of Biomedical Engineering, 2007)

Accuracy, efficiency and robustness of four algorithms allowing full sibship reconstruction from DNA marker data - K. Butler; C. Field; C. M. Herbinger; B. R. Smith (Molecular Ecology, 2004)
In the problem of reconstructing full sib pedigrees from DNA marker data, three existing algorithms and one new algorithm are compared in terms of accuracy, efficiency and robustness using real and simulated data sets. An algorithm based on the exclusion principle and another based on a maximization of the Simpson index were very accurate at reconstructing data sets comprising a few large families but had problems with data sets with limited family structure, while a Markov Chain Monte Carlo (MCMC) algorithm based on the maximization of a partition score had the opposite behaviour. An MCMC algorithm based on maximizing the full joint likelihood performed best in small data sets comprising several medium‐sized families but did not work well under most other conditions. It appears that the likelihood surface may be rough and presents challenges for the MCMC algorithm to find the global maximum. This likelihood algorithm also exhibited problems in reconstructing large family groups, due possibly to limits in computational precision. The accuracy of each algorithm improved with an increasing amount of information in the data set, and was very high with eight loci with eight alleles each. All four algorithms were quite robust to deviation from an idealized uniform allelic distribution, to departures from idealized Mendelian inheritance in simulated data sets and to the presence of null alleles. In contrast, none of the algorithms were very robust to the probable presence of error/mutation in the data. Depending upon the type of mutation or errors and the algorithm used, between 70 and 98% of the affected individuals were classified improperly on average.

Chemically-Enhanced Phytoextraction of Cadmium-Contaminated Soils Using Wheat (Triticum aestivumL.) - M. T. Begonia; G. B. Begonia; A. D. Butler; U. Griffin; C. Young (Bulletin of Environmental Contamination and Toxicology, 2003)

Relationship Between Six Years of Corn Yields and Terrain Attributes - Thomas C. Kaspar; Thomas S. Colvin; Daniel B. Jaynes; Douglas L. Karlen; David E. James; David W. Meek; Daniel Pulido; Howard Butler (Precision Agriculture, 2003)

Genetic Analysis of Susceptibility to Spontaneous and UV-Induced Carcinogenesis in Xiphophorus Hybrid Fish - Rodney S. Nairn; Steven Kazianis; Luis Della Coletta; David Trono; Andrew P. Butler; Ronald B. Walter; Donald C. Morizot (Marine Biotechnology, 2001)

Construction of an RFLP linkage map for cultivated sunflower - C. C. Jan; B. A. Vick; J. F. Miller; A. L. Kahler; E. T. Butler III. (Theoretical and Applied Genetics, 1998)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Some properties of adenylate kinase from chemolithotrophically grown Thiobacillus novellus - I. R. C. McKellar; A. M. Charles; B. J. Butler (Archives of Microbiology, 1980)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)